An evaluation of the effectiveness of volunteer community health workers in visiual acuity screening amongst residents residents aged 40 years and above in Beranang, Selangor - Hidayah NI; Che Muhaya M; Hanizah Y; Radziah AL; Rozila Y; Nasroum MN; Azizah O (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
A cross-sectional study on a household member aged 40 years and abov~ from households of 5 randomly sampled villages in Beranang, Hulu Langat Selangor between August 2000 to December 2000 was carried out to determine the effectiveness of volunteer community health workers in performing visual acuity screening as well as the prevalence of visual disabilities. It was found that the sensitivity and specificity of visual acuity screened by volunteers was 92.9% and 97.5% respectively when compared with health personnel. The prevelance oflow vision was 21.5% with the majority (55.4%) of those with low vison having cataracts.